Associations between Subjective Sleep Quality and Brain Volume in Gulf War Veterans. Issue 3 (1st March 2014) - Chao, Linda L.; Mohlenhoff, Brian S.; Weiner, Michael W.; Neylan, Thomas C.
Abstract: Study Objectives: To investigate whether subjective sleep quality is associated with brain volume independent of comorbid psychiatric conditions. Design: Cross-sectional. Setting: Department of Veterans Affairs (VA) Medical Center. Participants: One hundred forty-four Gulf War Veterans (mean age 45 years; range: 31-70 years; 14% female). Interventions: None. Measurements and Results: Total cortical, lobar gray matter, and hippocampal volumes were quantified from 1.5 Tesla magnetic resonance images using Freesurfer version 4.5. Subjective sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI). Multiple linear regressions were used to determine the association of sleep quality with total and regional brain volumes. The global PSQI score was positively correlated with lifetime and current posttraumatic stress disorder (PTSD) and current depressive symptoms (P < 0.001) and was higher in veterans with Gulf War Illness, trauma exposure, and those using psychotropic medication (P ≤ 0.03). After adjusting for these comorbid variables, age, intracranial volume, and multiple comparisons, global PSQI was inversely associated with total cortical and frontal gray matter volume (adjusted P ≤ 0.03). Within the frontal lobe, total PSQI was inversely associated with the superior and middle frontal, orbitofrontal, anterior cingulate, and frontal pole volumes (adjusted P ≤ 0.02). Examination of the 3-factor structure of the PSQI revealed that the associations were driven by perceived sleep quality. Conclusions: Poorer subjective sleep quality was associated with reduced total cortical and regional frontal lobe volumes independent of comorbid psychiatric conditions. Future work will be needed to examine if effective treatment of disturbed sleep leads to improved structural and functional integrity of the frontal lobes.